2021
DOI: 10.1039/d0py01535k
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the crystallinity and solubility of functional PCL with efficient post-polymerisation modification

Abstract: Poly(ε-caprolactone) is a semi-crystalline biocompatible polymer with good mechanical properties. Its crystallinity also uniquely enables poly(ε-caprolactone) to be used in different applications, from the development of 3D scaffolds for tissue...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Nevertheless, these reported PEAs were brittle, and more efforts are necessary to improve their material performance. To translate the recyclable polymers into useful materials in real applications, the tradeoffs between the recyclability and mechanical performance need to be well addressed. ,, It is well known that side groups can greatly influence the thermal and mechanical properties of polymers. We hypothesize that the introduction of the n -alkyl group at the 6-position of MDs could enhance the ductility of the PEAs while maintaining their mechanical strength as a consequence of hydrogen bonding interactions. Notably, these 6-substitued MDs with various side groups can be easily tailored from different aldehydes, which allows the facile tuning of PEA material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these reported PEAs were brittle, and more efforts are necessary to improve their material performance. To translate the recyclable polymers into useful materials in real applications, the tradeoffs between the recyclability and mechanical performance need to be well addressed. ,, It is well known that side groups can greatly influence the thermal and mechanical properties of polymers. We hypothesize that the introduction of the n -alkyl group at the 6-position of MDs could enhance the ductility of the PEAs while maintaining their mechanical strength as a consequence of hydrogen bonding interactions. Notably, these 6-substitued MDs with various side groups can be easily tailored from different aldehydes, which allows the facile tuning of PEA material properties.…”
Section: Introductionmentioning
confidence: 99%
“…1-hexanethiol, 1-octanethiol, 1-ethyl hexanethiol, 1-decanethiol, 1-dodecanethiol, and 1-hexadecanethiol) was also found to be thermoresponsive in n -dodecane. 151 The alkyl-functionalized polymers exhibited a UCST phase transition, which was dependent on the length of the alkyl thiol and the polymer concentration. The increase in the alkyl chain length on the PCL backbone from C6 to C12 resulted in an enhancement of its solubility in the hydrocarbon, and the polymers became semi-crystalline when the alkyl chain length reached 10 carbons, as demonstrated by DLS and UV-vis analyses.…”
Section: Hydrocarbonsmentioning
confidence: 99%
“…Clamor et al [78] reported a well-controlled ROP of ε-allyl caprolactone using Mg(BHT) 2 (THF) 2 to yield an allyl-functionalized lactone, ε-allyl-ε-caprolactone (AεPCL), suitable for post-polymerization modification with a 95% monomer conversion (Figure 13). The synthesized PCL was subsequently post-functionalized by photo-initiated thiol-ene addition on the pendant allyl-functionality using various alkyl thiols to produce lipophilic polyesters with tuned lipophilicity and crystallinity.…”
Section: Polyethersmentioning
confidence: 99%
“…The important toxicity aspect of poly(CL-AGE) [40], PEG-b-P(LA-co-AGE) [36], PGlCL [77], poly(ε-allyl-ε-caprolactone) [78], poly(ester-anhydride)s [48,50], polycarbonates [80], poly(1,1disubstituted-2-vinylcyclopropanes) [93], multiarm star polymers [89], bisallyl-functionalized telechelic polymers and star polymer [44], PEIene [66], and urethane-based allyl ether multiene monomers [62,63], which are discussed in this study, has not yet been evaluated, or at least not reported, in the reviewed articles.…”
Section: Toxicity Aspect Of the "Allyl" Functional Polymersmentioning
confidence: 99%